THE DEVELOPMENT OF MULTIMEDIA LEARNING USING THE MOODLE PROGRAM ON INTEGRAL SUBJECT FOR SENIOR HIGH SCHOOL STUDENTS IN GRADE XII - Isnaepi Isnaepi; Suparman Suparman (Universitas Ahmad Dahlan, 2018)
Multimedia learning on learning mathematics can help students visualize abstract materials to help students understand the material quickly. However, multimedia learning mathematics developed for the learning process of mathematics is only slightly. This research aims to develop multimedia learning using the MOODLE program on the integral subject for senior high school students in grade XII that feasible using on learning mathematics. This research is included in development research using the ADDIE development model. The research subjects are material experts, media experts, and State Senior High School 8 Yogyakarta (SMA Negeri 8 Yogyakarta) and State Senior High School 5 Yogyakarta (SMA Negeri 5 Yogyakarta). Data collection techniques used questionnaires, observations, and interviews conducted before developing the product. The research instruments used are observation guides, interview guides, and questionnaires to evaluate the learning multimedia that has been developed. The data analysis technique uses qualitative analysis that is converted into a Likert scale cumulative value. The result of the research showed that based on the analysis of multimedia learning needs, analysis of the characteristics of students, and analysis of problems encountered, obtained that methods of teaching teachers in monotonous, teachers who develop multimedia learning is only slightly, students often browsing related mathematics learning materials, students are difficult to understanding definite integral. Developed multimedia learning using the MOODLE program on the integral subject for senior high school students in grade XII that students quickly understood. The feasibility of developed products based on the calculation of average scores is an excellent category of material experts obtained for 4,37, excellent category of media experts obtained for 4,41, and decent category of students response obtained for 4,17. The student's response is decent, based on the result of the instrument of student response assessment.